The Effect Of Health Education With Animation Video Media On Students' Knowledge In Performing First Aid In Syncope - siti romadoni; Putri Nuraulia; Imardiani (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background : Fainting or syncope is a person's loss of consciousness ( LOC=Loss Of Consciousness ) caused by decreased blood flow to the brain. Syncope often occurs in students so knowledge of first aid in syncope is needed in the initial management so that it does not have a fatal impact and result in injury. It is estimated that there are 12 million cases of syncope in the world each year and in Indonesia as many as 35% of students have experienced syncope during school activities. Knowledge of first aid in syncope can be increased with health education using animated video media. Purpose: To determine the effect of health education using animated video media on students' knowledge in performing first aid for syncope. Methods: This research is a pre-experimental study using one group pretest and posttest with a quantitative research type . It's a sampling technique Simple Random Sampling, with a sample of 32 respondents. Data analysis using the Wilcoxon test. Results: Obtained the value of knowledge before the intervention was given at 11.00 and after the intervention was given at 15.00 with a p value of 0.01 < 0.05. Conclusion: there is an influence on the value of knowledge before and after being given first aid health education in syncope with animated video media .